Homemade remedies for poultry diseases used by rural households in Iyri-Suu, Kyrgyz Republic - Aldayarov, Nurbek; Tulobaev, Askarbek; Chekirov, Kadyrbai; Risvanli, Ali (Springer-Verlag Italia Srl, 2026)
This study documents and quantitatively analyses folk remedies used for poultry diseases in rural households of the Kyrgyz Republic. Semi-structured interviews were conducted with 84 participants across seven villages between March 2023 and October 2024. Ethnoveterinary data were evaluated using informant consensus factors (FIC) and use values (UV). A total of 803 homemade remedies were recorded, corresponding to 1,286 use reports. Treatments were derived from plant sources (57.5%), animal-based substances (29.5%), children's urine (2.5%), and a single chemical agent (10.5%). Eighteen plant species belonging to ten botanical families were identified, with dominant representation of Amaryllidaceae and Asteraceae. The highest use values were recorded for Allium cepa (UV = 0.88), Allium sativum (UV = 0.61), and Artemisia absinthium (UV = 0.59). The most frequently used plant materials were aerial parts and whole plants, primarily prepared as decoctions and infusions, while fresh and dried forms were commonly administered directly in feed. FIC values were consistently high across disease categories (0.93-0.96), indicating strong inter-household consensus in treatment practices. Artemisia absinthium was the only species used across all disease categories. Five distinct types of mixed-species herbal formulations were identified. In addition to phytotherapeutic remedies, animal-derived products, children's urine, and kerosene were also employed, reflecting limited access to formal veterinary services. Overall, ethnoveterinary practices constitute the primary healthcare system for household poultry, representing a structured, knowledge-consistent, and quantitatively robust traditional health-management framework in rural Kyrgyz communities.
Keywords: Ethnoveterinary Knowledge; Poultry Diseases; Plant Remedies; Animal Remedies; Rural Kyrgyz Households